Validation of an MBS Model of a Tram (Current Problems in Rail Vehicles, 2025)
The paper deals with the validation of an MBS (Multi-Body System) model of a three-section tram. Before the validation, the parameters of the model’s force elements were updated based on experimental data obtained from the manufacturers of the suspension components. The model validation was carried out based on measurement results obtained during stationary tests of the vehicle. The stationary tests included weighing of the manufactured trams, a bogie compression test, a determination of displacement characteristics test, and a twist test. To achieve the best agreement between the experimental data and the simulation results, key model parameter values were optimized using sensitivity analysis. Successful validation ensured the required credibility of the model for its use in simulation-based assessment of stationary ride characteristics as part of the vehicle homologation process.
Keywords: tram; validation; Multi-Body Simulation (MBS); model; stationary tests; rubber spring; vehicle weighing; bogie compression test; determination of displacement characteristics test; twist test; homologation process